Pi'uranga: Study of Cia-Cia's Nifas Period Treatment in the Bahari Village of Sampolawa District of South Buton Regency - Hasniah; La Ode Topo Jers; Wa Mame; Jamaluddin Hos (CV. Literasi Indonesia, 2020)
This research aims to find out the types of diseases that arise when the mother nifas does not do pi'uranga and how to perform pi'uranga on the Cia-cia in the Bahari Village. The theory used to read the data is Hippocrates' Humoral Pathology theory of healthiness or pain occurring depending on the balance of